2021
DOI: 10.1172/jci.insight.145029
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 overexpression rescues the RPE in mouse models of retinitis pigmentosa

Abstract: Nrf2, a transcription factor that regulates the response to oxidative stress, has been shown to rescue cone photoreceptors and slow vision loss in mouse models of retinal degeneration (rd). The retinal pigment epithelium (RPE) is damaged in these models, but whether it also could be rescued by Nrf2 has not been previously examined. We used an adeno-associated virus (AAV) with an RPE-specific (Best1) promoter to overexpress Nrf2 in the RPE of rd mice. Control rd mice showed disruption of the regular array of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 76 publications
5
29
0
Order By: Relevance
“…These results indicate that the therapeutic effect of Txnip does not require an inhibitory interaction with thioredoxins. This finding is in keeping with previous work which showed that anti-oxidation strategies promoted cone survival in RP mice (Komeima et al, 2006;Wu et al, 2021;Xiong et al, 2015). An additional mutation, S308A, which loses an AMPK/Akt-phosphorylation site on Txnip (Waldhart et al, 2017;Wu et al, 2013), was tested in the context of WT Txnip and in the context of the C247S allele.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…These results indicate that the therapeutic effect of Txnip does not require an inhibitory interaction with thioredoxins. This finding is in keeping with previous work which showed that anti-oxidation strategies promoted cone survival in RP mice (Komeima et al, 2006;Wu et al, 2021;Xiong et al, 2015). An additional mutation, S308A, which loses an AMPK/Akt-phosphorylation site on Txnip (Waldhart et al, 2017;Wu et al, 2013), was tested in the context of WT Txnip and in the context of the C247S allele.…”
Section: Resultssupporting
confidence: 86%
“…These combinations utilize cell type-specific promoters, reducing the chances of side effects from global expression of these genes. Of note, the Nrf2 expression was limited to the RPE, which we recently showed leads to much improved RPE survival and morphology in RP mice (Wu et al, 2021). Best1-Nrf2 was additive to RedO-Txnip for cone survival.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…To measure the effect of CD47 on cone survival, GFP-positive cones in the central retinas of rd1 mice were quantified. Cone counting using a GFP vector has been previously validated by our group and provides unambiguous labeling of cones, enabling automated quantification ( 4 , 9 , 10 , 23 ). At the doses used in this study, coinfection with 2 serotype 8 vectors in cones is expected to be at least 90% ( 4 ).…”
Section: Resultsmentioning
confidence: 99%